Perbandingan Pendapatan Usahatani Stevia Dengan Menggunakan Eco-Enzyme Dan Tanpa Eco-Enzyme - Angelica Paendong; Elsje Pauline Manginsela; Jenny Baroleh (Sam Ratulangi University, 2023)
This study aims to analyze the differences in revenue and income from the use of Eco-enzyme and without Eco-enzyme in Stevia plants. The research was conducted for 3 months from December 2022 to February 2023 at Stevia farm, Kolongan Atas II Village, Sonder District, Minahasa Regency. This research is a continuation of the Student Creative Program activities in 2022 funded by Sam Ratulangi University. The research data were collected using primary data obtained through structured observation, documentation, and data recording of all Stevia plant farming activities observed from upstream to downstream. The collection using secondary data was obtained through literature studies of previous research sourced from the internet such as google scholar, journals, books, and online newspapers based on the data needed in the study. Variables measured are the amount of Stevia leaf production, price, production costs, fixed costs, variable costs, revenue, income. The data analysis method used in this research is quantitatively by calculating the income from Stevia farming activities then the results that have been obtained are described in descriptive form. The results showed that there were differences in income results between the use of Eco-enzyme fertilizer and without Eco-enzyme. Stevia farming income with a planting area of 39 m2 using Eco-enzyme obtained IDR22.413,32 and without Eco-enzyme obtained -IDR71.566,68. Comparison of income results showed that Eco-enzyme is more profitable to be used in Stevia farming because of the increase in production which increases income.